+0  
 
0
50
4
avatar

Let f(x) be the polynomial f(x) = x^7 - 3x^3 + 2.

 

If g(x) = f(x+7), what is the sum of the coefficients of g(x)?

 Jun 15, 2022
 #2
avatar+124524 
+1

g (x) =  f (x + 7) =    (x + 7)^7  - 3(x + 7)^3  + 2    =

 

1x^7 + 49 x^6 + 1029 x^5 + 12005 x^4 + 84032 x^3 + 352884 x^2 + 823102 x + 822516

 

Just add the   red integers to get your answer

 

cool cool cool

 Jun 15, 2022
 #4
avatar+9458 
+1

Alternative solution:

 

The sum of coefficients of a polynomial \(p(x)\) is actually just \(p(1)\).

 

Proof: (You can omit this part if you just want the answer instead of the explanation.)

Let \(p(x) = a_n x^n + a_{n - 1}x^{n - 1} + a_{n - 2}x^{n - 2} + \cdots + a_2 x^2 + a_1 x + a_0\).

Then \(p(1) = a_n 1^n + a_{n - 1} 1^{n- 1} + \cdots + a_1 \cdot 1 + a_0 = a_n + a_{n -1} + a_{n-2} + \cdots + a_1 + a_0\), which is exactly the sum of coefficients of p(x).

 

Therefore, we just find \(g(1) = f(1 + 7) = f(8)\). The sum of coefficients of g(x) is \(f(8) = 8^7 - 3\cdot 8^3 + 2\).

 Jun 16, 2022

9 Online Users

avatar